At either end of the tube. (3rd May 2012) - Schyma, Barry M; Kerr, Robin; Alam, Shirjel
Abstract : This patient, who was a junior doctor when he was faced with open heart surgery, recounts his experience of postoperative intensive care, with help from his friend Robin Kerr to distinguish between hallucination and reality